2015
DOI: 10.1007/s12161-015-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Antioxidant Compounds and Antioxidant Activity of Sudanese Karkade (Hibiscus sabdariffa L.) Using Near Infrared Spectroscopy

Abstract: The extraction conditions applied in destructive analysis of Hibiscus sabdariffa L. (Hs) matrices before the measurement of antioxidant compounds may reduce their activities during isolation and purification due to decomposition. Hence, near infrared spectroscopic system was applied to determine these compounds. The calibration models developed by using partial least squares regression (PLSR) with 48 Hs samples and 24 unknown samples were used to confirm the robustness of the developed model. The results of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 46 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…DPPH free radical scavenging activity exhibited scavenging potential of ethanolic leaf extract of H. sabdariffa and C. caudatus in a concentration dependent manner. From the results, it was observed that H. sabdariffa showed a scavenging potential of 65.19 ± 1.63% at 500 lg/mL with an IC 50 value of 184.88 lg/mL which was comparatively higher than the previous report (Tahir et al 2016). Meanwhile, C. caudatus showed 57.86 ± 1.69% of free radical scavenging (Table 1).…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 73%
See 1 more Smart Citation
“…DPPH free radical scavenging activity exhibited scavenging potential of ethanolic leaf extract of H. sabdariffa and C. caudatus in a concentration dependent manner. From the results, it was observed that H. sabdariffa showed a scavenging potential of 65.19 ± 1.63% at 500 lg/mL with an IC 50 value of 184.88 lg/mL which was comparatively higher than the previous report (Tahir et al 2016). Meanwhile, C. caudatus showed 57.86 ± 1.69% of free radical scavenging (Table 1).…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 73%
“…H. sabdariffa is rich in protocatechuic acid and anthocyanin which enables the plant extracts in effective treatment of cancer, hypertension, inflammation, mutagenecity, leukaemia and gastrointestinal disorders (Mohd-Esa et al 2010;Yin et al 2011). H. sabdariffa extracts from calyces have been reported for significant antioxidant properties due to presence of bioactive compounds such as delphinidin-3-O-glucoside, delphinidin-3-O-sambubioside, cyanidin-3-O-sambubioside, polyphenolic compounds and organic acids (Formagio et al 2015;Tahir et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…H. sabdariffa calyces are commonly used for the preparation of tea and infusions. The red drink is widely consumed directly or it is an ingredient in the preparation of some foods, such as juice, jam, pudding, gelatin, and desserts [24]. Moreover, it is well known in traditional medicine for its diuretic and mild laxative effects.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological properties of HS have been extensively studied for years, preparing extracts using several solvents (water, alcohols alone or in mixtures) and evaluating their biological effects [8,9,10,11,12,13,14,15]. All the HS extracts are characterized by the presence of phenols, polyphenols, anthocyanins and organic acids, such as citric, tartaric, malic, ascorbic acids and others, which are responsible for high antioxidant and anti-inflammatory properties [16,17,18,19]. These functions enhance the healing process by modulating the production of reactive oxygen species and pro-inflammatory cytokines that are responsible for the amplification of the damage [20].…”
Section: Introductionmentioning
confidence: 99%